The influence of haematocrit on quality control parameters in plateletpheresis procedure - Svetlana Jović Lacković; Sunita Delić Ćustendil; Aida Žabić; Ahida Suljkanović Mahmutović; Sabina Čamdžić Smajić; Alma Osmić Husni (Medicinski glasnik, 2025)
Aim: Plateletpheresis is a specialized procedure that collects platelets from peripheral blood using a cell separator. Platelet concentrates obtained by apheresis have better content in terms of better functionality and viability of platelets, reduced risk of infection with blood transmissive viruses and HLA-sensitization. The aim of the study was to examine the influence of donors’ predonation haematocrit on the value of quality control parameters in the plateletpheresis product, to determine the frequency of adverse events and its relation to the predonation haematocrit value of donors. Methods: A retrospective analysis included the total number of performed plateletpheresis in the period between 1 January 2022 and 31 December 2023 at the Polyclinic for Transfusion Medicine in University Clinical Centre of Tuzla. Two groups of platelet donors with haematocrit <45% and haematocrit ?45% and quality control parameters in both groups were compared. Results: A total of 73 donors with Hct<45%, and a total of 43 donors with Hct?45% was found. The total volume of processed blood was significantly higher in the group of donors with Hct ?45% (p<0.0001). The duration of the plateletpheresis was significantly longer in donors with higher haematocrit (p=0.003). Conclusion: The level of haematocrit in the donor significantly affected the duration of the procedure and the consumption of resources, but the quality of the final product did not deviate much from the values recommended by the International Society for Blood Transfusion (ISBT) and the American Association of Blood Banks (AABB).
Keywords: donor; cell separator; transfusion